2020
DOI: 10.1186/s12872-020-01338-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher incidence of perivalvular abscess determines perioperative clinical outcome in patients undergoing surgery for prosthetic valve endocarditis

Abstract: Background: Cardiac surgery for prosthetic valve endocarditis (PVE) is associated with substantial mortality. We aimed to analyze 30-day and 1-year outcome in patients undergoing surgery for PVE and sought to identify preoperative risk factors for mortality with special regard to perivalvular infection. Methods: We retrospectively analyzed data of 418 patients undergoing valve surgery for infective endocarditis between January 2009 and July 2018. After 1:1 propensity matching 158 patients (79 PVE/79 NVE) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Besides these, native valve was the most common involved. Patients undergoing surgical treatment for prosthetic valve endocarditis had a higher 30day and 1-year mortality, when compared to native valve endocarditis [19]. The proportion of congenital heart disease, which was associated with better outcome than other forms of IE [7], was higher in our study [9,10].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Besides these, native valve was the most common involved. Patients undergoing surgical treatment for prosthetic valve endocarditis had a higher 30day and 1-year mortality, when compared to native valve endocarditis [19]. The proportion of congenital heart disease, which was associated with better outcome than other forms of IE [7], was higher in our study [9,10].…”
Section: Discussionmentioning
confidence: 68%
“…Some studies have also confirmed that these factors were associated with in hospital mortality [8,[22][23][24][25][26]. And perivascular abscess [19], diabetes mellitus [27,28], or acute renal failure [26,29] have also been reported to be the risk factors of high mortality. Interestingly, medical therapy was associated with higher in-hospital mortality, which suggested the protective role of surgical treatment.…”
Section: Discussionmentioning
confidence: 89%
“…PVE is a dreadful complication after open-heart valve surgery and has been noted to occur in 1% to 6% after heart valve surgery with an incidence of 0.3 to 1.6 per patient-year. 4 Several studies have identified PVE as an independent risk factor of inhospital mortality, 15,16 with many clinicians considering PVE even a separate disease from native IE. 17 Despite the existing evidence in the literature and the fact that PVE was slightly more prevalent in the Staphylococcus group, PVE was not identified as an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Perivalvular abscess formation is associated with a more aggressive disease course and worse outcomes; it is more commonly seen as a complication of PVE, especially aortic PVE, and it appears to occur more often in endocarditis caused by S. aureus . 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…Apart from the management of its possible complications, the mainstay of treatment for infective endocarditis remains appropriate antibiotic therapy and early surgery, which becomes mandatory in cases with locally uncontrolled infection, heart failure or lesion at high risk of embolization. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%